2002
DOI: 10.1287/mnsc.48.3.364.7731
|View full text |Cite
|
Sign up to set email alerts
|

Network Ties, Reputation, and the Financing of New Ventures

Abstract: Explaining how entrepreneurs overcome information asymmetry between themselves and potential investors to obtain financing is an important issue for entrepreneurship research. Our premise is that economic explanations for venture finance, which do not consider how social ties influence this process, are undersocialized and incomplete. However, we also argue that organization theoretic arguments, which draw on the concept of social obligation, are oversocialized. Drawing on the organizational theory literature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
961
5
31

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,301 publications
(1,030 citation statements)
references
References 50 publications
33
961
5
31
Order By: Relevance
“…As previous research has shown higher education is particularly important for making progress in a high-potential project (Samuelsson and Davidsson 2009;Obschonka et al 2011) we include the dummy variable PhD degree into the regressions. Social capital appears to be conducive for nascent entrepreneurs in providing access to novel information and trusted feedback concerning business strategies (Uzzi 1997), in product development (Lechner and Dowling 2003) and in getting into contact with potential investors (Shane and Cable 2002). The exact measurement of social capital, however, is subject to controversial debates.…”
Section: Control Variablesmentioning
confidence: 99%
“…As previous research has shown higher education is particularly important for making progress in a high-potential project (Samuelsson and Davidsson 2009;Obschonka et al 2011) we include the dummy variable PhD degree into the regressions. Social capital appears to be conducive for nascent entrepreneurs in providing access to novel information and trusted feedback concerning business strategies (Uzzi 1997), in product development (Lechner and Dowling 2003) and in getting into contact with potential investors (Shane and Cable 2002). The exact measurement of social capital, however, is subject to controversial debates.…”
Section: Control Variablesmentioning
confidence: 99%
“…The literature suggests that top managers play an important role in new venture success (e.g., Eisenhardt and Schoonhoven, 1990;Keeley and Roure, 1990;McGee, Dowling, and Megginson, 1995). Managers can generally offer two types of resources: human capital as indicated by their experience (Eisenhardt and Schoonhoven, 1990;McGee et al, 1995) and social capital as indicated by their external ties (Granovetter, 1985;Shane and Cable, 2002 develop competitive advantage, and to achieve better performance (Barney, 1991).Previous studies in this area are mainly limited to new ventures operating in Western developed markets with relatively stable institutional environments. Yet little is known about how managerial resources are related to new venture performance in transition economies that are experiencing significant institutional changes in moving from central planning to market competition.…”
mentioning
confidence: 99%
“…Researchers observed this behavioral pattern in studies on hiring (Fernandez & Weinberg, 1997;Williamson & Cable, 2003), financing (Shane & Cable, 2002), investing (Cohen, Frazzini, & Malloy, 2008) and strategic decision making (Geletkanycz & Hambrick, 1997;Carpenter & Westphal, 2001). Overall, these studies suggest that employees' use of their social capital benefits firm performance.…”
Section: Introductionmentioning
confidence: 81%
“…We focus on worker allocation decisions, as these are among the most important resource allocation decisions in firms. While previous work has frequently engaged in testing one of both aspects in isolation (Fernandez & Weinberg, 1997;Shane & Cable, 2002;Williamson & Cable, 2003;Cohen et al, 2008;Geletkanycz & Hambrick, 1997;Peng & Luo, 2000;Collins & Clark, 2003), no previous study has been able to estimate both effects from the same data. We thus provide a novel approach of examining the economic consequences of social ties.…”
Section: Introductionmentioning
confidence: 99%